Система поддержки принятия решений при проведении лечебно-диагностических мероприятий - Поворознюк, Анатолий Иванович (НТУ "ХПИ", 2014)
Формализованы этапы лечебно-диагностического процесса при разработке компьютерных систем поддержки принятия решений в медицине. Для комплексной оценки этапов лечебно-диагностического процесса с целью минимизации рисков врачебных ошибок разработан метод кластеризации диагнозов в пространстве фармакологических действий и коррекции порогов в диагностическом решающем правиле. Архитектура программного обеспечения системы позволяет легко адаптироваться к различным предметным областям медицины.

The paper analyzed and examined by a complex of diagnostic and treatment facilities, which consists of interdependent stages of diagnosis and treatment of identified pathologies. The Formalized stages diagnostic-medical process at development computer decision support system in medicine. For complex estimation stage diagnostic-medical process for the reason minimization risk doctor-mistake is designed method to clusterizations diagnosis in space pharmacological action and correction threshold in diagnostic solving rule. Success of the proposed information system is determined by the choice of the target platform development, as well as a well-designed architecture, which in the future will provide the scalability, flexibility, and ease of system maintenance. Efficiency and effectiveness of the system is exemplified in its testing on real medical data using the training sample of 100 patients.
Decision support system when undertaking diagnostic-medical action
Keywords: компьютерная система; медикаментозное лечение; фармакологическое действие; врачебная ошибка; computer system; decision making; diagnostics; pharmacological action; doctor-mistake